In vitro/in silico prediction of drug induced steatosis in relation to oral doses and blood concentrations by the Nile Red assay. (1st September 2022) - Brecklinghaus, Tim; Albrecht, Wiebke; Duda, Julia; Kappenberg, Franziska; Gründler, Lisa; Edlund, Karolina; Marchan, Rosemarie; Ghallab, Ahmed; Cadenas, Cristina; Rieck, Adrian; Vartak, Nachiket; Tolosa, Laia; et al.
Abstract: The accumulation of lipid droplets in hepatocytes is a key feature of drug-induced liver injury (DILI) and can be induced by a subset of hepatotoxic compounds. In the present study, we optimized and evaluated an in vitro technique based on the fluorescent dye Nile Red, further named Nile Red assay to quantify lipid droplets induced by the exposure to chemicals. The Nile Red assay and a cytotoxicity test (CTB assay) were then performed on cells exposed concentration-dependently to 60 different compounds. Of these, 31 were known to induce hepatotoxicity in humans, and 13 were reported to also cause steatosis. In order to compare in vivo relevant blood concentrations, pharmacokinetic models were established for all compounds to simulate the maximal blood concentrations (Cmax ) at therapeutic doses. The results showed that several hepatotoxic compounds induced an increase in lipid droplets at sub-cytotoxic concentrations. To compare how well (1) the cytotoxicity test alone, (2) the Nile Red assay alone, and (3) the combination of the cytotoxicity test and the Nile Red assay (based on the lower EC10 of both assays) allow the differentiation between hepatotoxic and non-hepatotoxic compounds, a previously established performance metric, the Toxicity Separation Index (TSI) was calculated. In addition, the Toxicity Estimation Index (TEI) was calculated to determine how well blood concentrations that cause an increased DILI risk can be estimated for hepatotoxic compounds. Our findings indicate that the combination of both assays improved the TSI and TEI compared to each assay alone. In conclusion, the study demonstrates that inclusion of the Nile Red assay into in vitro test batteries may improve the prediction of DILI compounds. Graphical Abstract: ga1 Highlights: Drug-induced lipid droplet accumulation can be quantified by the Nile Red assay in HepG2 cells. The Nile Red assay improves the separation of hepatotoxic and non-hepatotoxic substances. The improved separation is evidenced by the Toxicity Separation Index (TSI). For several steatosis inducing compounds the Nile Red assay resulted in lower effective concentrations than a viability test.